Birth order and intrahousehold allocation of food: Unequal allocation for unwanted children - Saputra, Aditya Bagus; Handayani, Dwini (Social, Ecology, Economy for Sustainable Development Goals Journal, 2024)
Background: Food allocation is a fundamental aspect within households, seemingly capable of being distributed evenly among household members, especially among siblings. However, several factors can lead to differences in food allocation among siblings. Method: Using data from IFLS 4 and 5, with food variety as a proxy for food allocation, this study examines two influential factors on food allocation: birth order and imperfect fertility control status. Additionally, this study attempts to elucidate the mechanism of the birth order effect using the aforementioned imperfect fertility control status. FIndings: The findings of this study reveal a negative effect of birth order on household food allocation. Moreover, children with undesired status or belonging to families with undesired status due to imperfect fertility control tend to have lower food variety. Conclusion: However, this study cannot causally explain the mechanism behind the negative effect of birth order through imperfect fertility control status. Novelty/Originality of this article: This study analyzes the effects of birth order and fertility control status on household food allocation, finding adverse effects of birth order and unwanted status on food variation. As a novelty, this study proposes the development of a family-based nutrition intervention program that considers intra-household dynamics, aiming to reduce the gap in food allocation between siblings and improve children's overall nutritional status.